IMAJINASI KREATIF DALAM PENGALAMAN MI'RAJ IBN ARABI - Kamaliah, Alfi (Living Islam: Journal of Islamic Discourses, 2021)
This article aims to explain the role of imagination in the mi'raj experienced by Ibn Arabi. Ibn Arabi is known as the foremost mystic in the Islamic world. His mystical thoughts can be found in his books. One of the mystical aspects experienced by Ibn Arabi is mi'raj. Ibn Arabi's mi'raj experience was different from that of the Prophet Muhammad. The Mi'raj of the Prophet was carried out by means of the body and spirit and received a new shari'a, while the mi'raj experienced by Ibn Arabi was carried out with the spirit and did not receive a new shari'a. The mi'raj experience will be analyzed using a creative imagination approach. The results of this study show three roles of imagination from Ibn Arabi's mi'raj experience. First, his creative imagination can create an intermediate realm or what is called the imaginal realm. In this Ibn Arabi could meet the spirituality of the previous prophets. Second, the imagination is interpreted by Ibn Arabi as the power of creative thinking. Ibn Arabi combined two sciences, namely the science of reason and Islamic gnosticism to create new knowledge about mi'raj. Third, the imagination has a bissociative function. Ibn Arabi dared to risk being called a strange Sufi with his new knowledge of mi'raj.Keyword: Ibn Arabi, Mi'raj, Creative Imagination, Bissociative FunctionArtikel ini bertujuan untuk menjelaskan peran imajinasi dalam pengalaman mi’raj yang dialami oleh Ibn Arabi. Ibn Arabi dikenal sebagai mistikus terkemuka di dunia Islam. Pemikiran mistiknya dapat ditemukan dalam kitabnya. Salah satu aspek mistik yang dialami oleh Ibn Arabi adalah mi’raj. Pengalaman mi’raj Ibn Arabi berbeda dengan mi’rajnya Nabi Muhamamd. Mi’rajnya Nabi dilakukan dengan cara jasad dan ruh dan mendapatkan syariat baru, sedangkan mi’raj yang dialami oleh Ibn Arabi dilakukan dengan ruh dan tidak mendapat syariat baru. Pengalaman mi’raj tersebut akan dianalisis dengan menggunakan pendekatan imajinasi kreatif. Hasil penelitian ini menunjukkan tiga peran imajinasi dari pengalaman mi’rajnya Ibn Arabi. Pertama, imajinasi kreativnya dapat menciptakan alam antara atau yang disebut dengan alam imajinal. Di alam ini Ibn Arabi dapat bertemu dengan ruhaniah para nabi terdahulu. Kedua, imajinasi dimaknai oleh Ibn Arabi sebagai daya kreativitas berpikir. Ibn Arabi mengkombinasikan dua ilmu yakni ilmu nalar dan gnostik Islam untuk membuat pengetahuan baru tentang mi’raj. Ketiga, imajinasi tersebut memiliki fungsi bisosiatif. Ibn Arabi berani mengambil resiko dikatakan sufi yang aneh dengan pengetahuan barunya tentang mi’raj.Keyword: Ibn Arabi, Mi’raj, Imajinasi Kreatif, Fungsi Bisosiatif